65 Elevated levels of cathepsin S is associated with inflammation and pathological remodelling in heart failure with preserved ejection fraction. (16th October 2019) - Russell-Hallinan, A; Glezeva, N; McDonald, I; Cooke, G; Ledwidge, M; McDonald, K; Burden, R; Watson, C
Abstract : Background: Heart failure with preserved ejection fraction (HFpEF) is a complex clinical syndrome associated with significant morbidity and mortality. Microvascular inflammation, endothelial dysfunction and increased extracellular matrix (ECM) deposition have been proposed as major pathophysiological factors, where the systemic pro-inflammatory state arising from co-morbidities such as obesity, diabetes and hypertension is predictive for HFpEF. Lysosomal proteases, such as the cathepsin family, play an important role in degradation of cellular substrates and remodelling of the extracellular matrix (ECM). Cathepsin S (CatS) is thought to be a particularly potent cysteine protease cleaving elastin and generating bioactive elastin peptides. Recent reports have highlighted altered levels of CatS in conditions of cardiac stress, remodelling, and dysfunction, however, whether alterations of CatS are present in the clinical scenario of HFpEF remains to be determined. Purpose: This study investigated whether levels of CatS are altered in HFpEF patients and if there is an association with CatS and pathophysiological cardiac processes such as inflammation and fibrosis. Methods: This work spanned three different cohorts. Cohort 1: Levels of CatS were examined in serum samples of n=199 non heart failure (non-HF) and n=70 HFpEF patients by ELISA. Cohort 2: Gene expression of CatS and inflammatory markers were examined in monocytes isolated and purified from peripheral blood of n=30 non-HF and n=17 HFpEF patients. Cohort 3: Myocardial tissue and peripheral serum samples were procured from n=37 stable patients undergoing elective cardiac-bypass surgery. Samples were analysed for CatS levels and fibro-inflammatory markers relevant to cardiac fibrosis by qPCR, ELISA and radio-immuno assays. Results: HFpEF patients had significantly higher levels of serum CatS compared with non-HF controls. CatS gene expression in isolated peripheral monocytes significantly correlated with markers of both classical (CCR2) and alternative (CD163, CX3CR1 and matrix metalloproteinase 9) activation. Myocardial CatS gene expression was positively correlated with the hypoxia marker carbonic anhydrase IX, tumour necrosis factor alpha, procollagen C-proteinase, matrix metalloproteinase 1, and lysyl oxidase gene expression. Similarly, serum levels of CatS correlated with both pro-inflammatory (IL-6, IL-8, MCP-1 and TNFα) and pro-fibrotic (PICP, PIINP and TIMP-1) markers. Conclusion: Cathepsin S is significantly elevated in the sera of HFpEF patients and correlates with pathological processes including inflammation, hypoxia and ECM remodelling. Therapeutically targeting this cysetine protease may yield a novel strategy for the treatment of HFpEF.